Getting the mouse out of the box: Tool innovation in preschoolers - Voigt, Babett; Pauen, Sabina; Bechtel-Kühne, Sabrina (Journal of experimental child psychology, 2019)
Following the literature, children younger than 8years rarely innovate a tool. Theories on innovation and comparative research on tool manufacturing suggest that children’s performance may depend on the task context. The current study explored whether preschool children’s poor performance in past research could be attributed to short time limits and the required manufacturing method. In four experiments, 5-year-olds needed to retrieve a toy from a tube by manufacturing a novel tool and using it successfully. The type of potentially functional materials varied among the experiments. Cumulative innovation rate was analyzed after 1 and 10min. The 5-year-olds rarely innovated if merely “reshape” (modifying the material’s shape) was offered as a potentially successful manufacturing method even when they had up to 10min to complete the task (21%; Experiment 1). The vast majority of 5-year-olds succeeded if multiple manufacturing strategies were functional, but only if children had up to 10min to complete the task (93%; Experiment 2). The innovation rate remained high if “detach” (separating material from a substrate) was not available (76%; Experiment 3) and if “subtract” (removing something from a material) was the only functional manufacturing method (71%; Experiment 4). Our findings suggest that even preschool-aged children are “good innovators” if (a) they have enough time and (b) manufacturing methods other than reshape can be used to solve the problem. However, they seem to struggle if (a) they have only 1min to complete the task and (b) solving the task requires them to reshape a material.
Gesehen am 04.07.2019